MERUNGKAI MAKNA SAJAK “ISTIMEWANYA KITA” : PENGAPLIKASIAN SEMANTIK INKUISITIF DALAM KALANGAN MURID TAHUN EMPAT - GEORGE ROMIKO, BUJANG; Mary Fatimah, Subet (UKM, 2021)
The aim of this study is to explain the actual meanings implicated in language arts’ materials in Year 4 Malay Language Textbook via Inquisitive Semantic analysis (IS) introduced by Nor Hashimah Jalaluddin (2014). This is a qualitative research. Text method analysis on language arts’ materials extracted from Year 4 Malay Language Textbook was carried out as well as observation on 10 pupils of Year 4 as respondents of this study. The results showed that language arts’ materials such as poems can create questions which can be related to pupils’ high order thinking skills (HOTS). In addition, this study found that there were implied meanings when the inquisitive semantic approach analysis was performed in stages starting with the semantic script's analysis, semantic resonance’s analysis and subsequently inquisitive semantic analysis. The application of Relevance Theory founded by Sperber and Wilson (1986, 1995) enhanced further the analysis done at the second stage of semantic resonance’s analysis whereby the subject of Malay language can be combined with various other disciplines. Hence, the learning of these subjects become more interesting and multi-disciplinary. This study is expected to provide a new approach to educators, especially Malay language teachers at the primary education level, to plan a more challenging and enjoyable teaching and learning experience to ensure a better and meaningful learning impact for students.